2023
DOI: 10.3390/w15101941
|View full text |Cite
|
Sign up to set email alerts
|

Sand Spit Morphology at an Inlet on Phu Quoc Island, Vietnam

Abstract: Tidal inlets with attached sand spits are a very common coastal landform. Since the evolution of sand spits along coastlines influence the social-economic development of local coastal areas, sand spits have become the objects of numerous studies. However, previous studies have mainly focused on sand spits that are usually in the scale of hundreds of meters in width, whilst knowledge about the evolution of smaller-scale sand spits still remains limited. Therefore, in this study, the morphological change of a sm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Landsat imagery has been applied intensively in coastal studies, especially in areas with significant shoreline temporal variations, such as the mouths of rivers, sand spits, and around coastal structures [27,[30][31][32][33][34]. In this research, Landsat images spanning the period 1987 to 2023 were gathered (as shown in Table 1) to monitor alterations in the shorelines surrounding the mouth of the Ma River.…”
Section: Landsat Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Landsat imagery has been applied intensively in coastal studies, especially in areas with significant shoreline temporal variations, such as the mouths of rivers, sand spits, and around coastal structures [27,[30][31][32][33][34]. In this research, Landsat images spanning the period 1987 to 2023 were gathered (as shown in Table 1) to monitor alterations in the shorelines surrounding the mouth of the Ma River.…”
Section: Landsat Image Analysismentioning
confidence: 99%
“…The along-shore and cross-shore coordinates of the cuspate tips on both sides of the mouth of the Ma River were observed and are used for discussing the morphological be havior of the river's mouth. The method of using the coordinates of special points such as the tips of sand spits or the center of gravity to discuss the evolution of a sand body has been applied widely in coastal engineering [27,30,32,34,44,45]. Figure 6 illustrates the schematic for measuring the coordinates of the cuspate tips, which are considered the most prominent protrusions into the open water.…”
Section: Evolution Of the Cuspate Deltamentioning
confidence: 99%
“…The offshore wave data extracted from the WaveWatch III model [43] were transformed to the nearshore using the COASTEXCEL tool [60]. Duy et al [61] applied and validated the wave transformation tool at the Phu Quoc island in Vietnam, which showed good agreement with measured datasets. Furthermore, inaccuracies in estimating the depth of closure may also arise from Equation ( 6) coefficients, wave reanalysis products, and coastal structures' presence [62][63][64].…”
Section: Depth Of Closure and Berm Heightmentioning
confidence: 99%
“…Landsat imagery has been applied intensively for coastal studies especially in areas with significant temporal variation of the shorelines such as as river mouths, sand spits, and around coastal structures [26][27][28][29][30][31]. In this study, Landsat images from 1987 to 2023 were collected (Table 1) for mapping the changes of the shorelines around the Ma River mouth.…”
Section: Landsat Image Analysismentioning
confidence: 99%
“…In this section, the along-shore and cross-shore coordinates of the cuspate tips on both sides of Ma River mouth will be measured and used for discussing the morphological behavior of the river mouth. The method of using the coordinates of special points such as sand spit's tips or the central of gravity to discuss the evolution of a sand body has been applied widely in coastal engineering [26,28,29,31,41,42]. Figure 5 illustrates the schematic for measuring the coordinates of the cuspate tips, which are considered as the most prominent protrusions into the open water.…”
Section: Evolution Of the Cuspate Deltamentioning
confidence: 99%